Separation of antibody helper and antibody suppressor human T cells by using soybean agglutinin. - Reisner, Y (1980)
Soybean agglutinin (SBA) binds specifically to mouse B cells and has been used in the past to separate mouse B and T spleen cells by differential agglutination of the B cells. In the present study it was found that a major T-cell subpopulation of human peripheral blood mononuclear cells is agglutinated by SBA along with the B cells and monocytes. Tests of such cell surface markers as Fc receptors for IgG and IgM, as well as functional assays of antibody production by B cells, revealed that the SBA-agglutinated cell fraction contains the antibody helper T cells whereas the unagglutinated fraction is enriched with antibody suppressor T cells. Similar observations were made in tests of the proliferative response to mumps antigen. A recently prepared monoclonal antibody, anti-Leu 2a, which recognized the same thymus-dependent antigen previously defined by a heterologous anti-human T cell serum (alpha TH2), was found to define by indirect immunofluorescence a subpopulation of SBA- cells of intermediate staining intensity which was not detectable in the SBA+ population.